Fiscal policy in EMU: Towards a sustainability and growth pact? - Benoît Coeuré; Jean Pisani-Ferry (Bruegel, 2005)
[Introduction ...] The goal of this contribution is to take stock of the academic and policy discussions on the fiscal institutions of EMU, to confront the framework in place with what is known of the desirable properties of fiscal policy in a monetary union, and to discuss possible improvements. It is organised as follows. In section 2, we discuss the EMU fiscal framework. In section 3, we describe EMU fiscal policy since 1999 and we assess the effectiveness of the SGP. In section 4, we outline a “Sustainability and Growth Pact” with a view to putting flesh on the revised Pact and we draw our conclusions.
Keywords: 330; Finanzpolitik; Eurozone; Europäischer Stabilitätsmechanismus; EU-Staaten